2012
DOI: 10.1002/aqc.2234
|View full text |Cite
|
Sign up to set email alerts
|

Wetland habitats of the Sabana de Bogotá Andean Highland Plateau and their birds

Abstract: 1. The Sabana de Bogotá highland plateau is located in the eastern Andes wetland complex of Colombia, a biogeographically important and highly degraded area where little is known about the general habitat availability and requirements for wildlife based on comparative studies.2. This study sought to identify the environmental factors that best explained the richness and composition of bird communities in the area's wetlands.3. GIS and remote images were used to measure landscape and local habitat variables alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
2
11
2
4
Order By: Relevance
“…Our finding that lagoon size plays a minor role in waterbird habitat use is somewhat unusual (Riffel et al, 2001;Rosselli and Stiles, 2012;Sebastián-González and Green, 2014), although a few earlier studies have obtained similar results. For example, Guadagnin et al (2009) found that waterbird abundance decreased with increasing area of fragmented wetlands in South Brazil.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our finding that lagoon size plays a minor role in waterbird habitat use is somewhat unusual (Riffel et al, 2001;Rosselli and Stiles, 2012;Sebastián-González and Green, 2014), although a few earlier studies have obtained similar results. For example, Guadagnin et al (2009) found that waterbird abundance decreased with increasing area of fragmented wetlands in South Brazil.…”
Section: Discussionsupporting
confidence: 73%
“…High vegetation can have negative effects for wading birds and gulls by impairing prey detectability and site selection (Butler and Gillings, 2004;Tavares et al, 2013), but it constitutes a suitable habitat for other groups such rallids and ciconids (Jedlikowski et al, 2014;Tavares and Siciliano, 2013b). Finally, a clear positive relationship has been observed between wetland size, habitat heterogeneity and waterbird species richness and abundance (Elmberg et al, 1994;Rosselli and Stiles, 2012;Sebastián-González and Green, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…This is related to the increase in some species such as G. galeata and decrease in probers like Gallinago and Tringa spp. (Rosselli and Stiles, 2012a). The increase in the shrub vegetation around the edges of some wetlands has probably induced the increment in S. subpudica and perhaps also T. aedon.…”
Section: "Natural" Changes In Some Habitatsmentioning
confidence: 99%
“…Although, in 2000 the city's authorities declared 12 wetlands as ecological parks for conservation, the pressure from urbanization continues, including increased pollution, encroachment of the borders and further reduction of wetland areas, and increasing presence of domestic dogs (Rosselli and Stiles, 2012a). …”
Section: Study Areamentioning
confidence: 99%
“…Sabana de Bogotá complex of wetlands together with the Cundiboyacense wetlands form a region that is one of the most biodiverse regions in the world [30]. Despite the fact that this region has a rich and distinctive avifauna, these wetlands are highly affected by pollutants mostly from agricultural activities and new urbanization [32]. Because of this, the EPP is developing plans to restore these wetlands.…”
Section: Study Datamentioning
confidence: 99%